Estudio de la violencia física a la mujer conforme los casos de femicidios, debido a su condición se ha llegado a la discriminación y desigualdad - Saltos Viñan, Thalia Nathaly (2023)
The present degree work is titled "Study of physical violence against women in cases of femicide, due to their condition they have been discriminated against and unequal," and its interest in investigating and analyzing is due to the violation of women's rights because of their gender, transgressing their rights and creating inequality with respect to men. It is essential to understand gender violence and contribute to the fight against it, which, as personal experiences motivate working in this field to help other people in similar situations. Showing gender equality and social justice, they see this work as a way to advocate for these causes, this challenging topic requires great dedication and effort. It is important to highlight physical violence in Ecuador because it is a problem that affects many women in the country and has severe social, psychological, and physical consequences. Understanding this topic allows us to comprehend the gravity of the problem and take measures to prevent and combat it. Moreover, knowledge about physical violence in Ecuador helps us identify the underlying causes of the problem and work on sustainable and effective solutions to eradicate it. It is also important to know about physical violence in Ecuador because it allows us to understand how this problem is related to other social issues such as discrimination, inequality, and social exclusion, 4 which are fundamental in addressing this problem effectively and ensuring women's rights and safety in the country. According to data from the National Institute of Statistics and Censuses (INEC), 67% of women in Ecuador have suffered some form of violence in their life, with physical violence being one of the most common types. In addition, according to the National Observatory of Gender Violence, at least 71 femicide cases were registered in the country in 2020, demonstrating the seriousness of the problem. It is also important to mention that physical violence against women in Ecuador occurs in different areas, including home, community, work, and education, and is often perpetrated by current or former romantic partners. Furthermore, physical violence is more frequent in women belonging to vulnerable groups, such as indigenous, Afro-Ecuadorian, or migrant women. The study shows that physical violence against women has increased irrationally, constituting femicide as the norm violated, a crime that is typified in our comprehensive criminal code in article 141, which typifies the murder of a woman due to her gender. This degree work was carried out using materials and methods that allowed its development, including surveys and interviews with legal professionals, whose results were used to propose a legal proposal to guarantee women's rights in their family environment to achieve the effective exercise of their rights, which, despite existing laws, are still being violated.